(R)-3-(8'-Hydroxyfarnesyl)-indole and other chemical constituents from the flowers of Anomianthus dulcis and their antimalarial and cytotoxic activities - Thanika Promchai (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. A new farnesylindole, (R)-3-(8'-hydroxyfarnesyl)-indole (1), as a scalemic mixture (33% ee) along with nine known compounds (2-10), including one farnesylindole, three flavanones, three flavone derivatives and two chalcone derivatives were isolated from the methanolic crude extract of the flowers from Anomianthus dulcis. All compounds were purified by appropriate chromatographic techniques and their structures elucidated by spectroscopic methods. Compounds 1, 2 and 8 showed moderate antiplasmodial activities against TM4/8.Two and K1CB1 strains of which compound 2 displayed the best activity with IC50 values of 27.9 ± 2.57 and 21.4 ± 1.68 µM, respectively. In addition, compound 1 also presented modest cytotoxicity against a KB cell line with an IC50 value of 22.3 ± 0.39 µM. None of these compounds showed cytotoxicity against Vero cells.